Simulated climate change and atrazine contamination can synergistically impair zebrafish testicular function - Souza, Victor Ventura de; Moreira, Davidson Peruci; Braz-Mota, Susana; Valente, Wanderson; Cotta, Gustavo Caldeira; Rodrigues, Maira da Silva [UNESP]; Nóbrega, Rafael Henrique [UNESP]; Corrêa, Rebeca Dias Serafim; Hoyos, Daniela Chemin de Melo; Sanches, Eduardo Antônio [UNESP]; Val, Adalberto Luís; Lacerda, Samyra Maria dos Santos Nassif (Elsevier, 2024)
Elements that interfere with reproductive processes can have profound impacts on population and the equilibrium of ecosystems. Global warming represents the major environmental challenge of the 21st century, as it will affect all forms of life in the coming decades. Another coexisting concern is the persistent pollution by pesticides, particularly the herbicide Atrazine (ATZ), which is responsible for a significant number of contamination incidents in surface waters worldwide. While it is hypothesized that climate changes will significantly enhance the toxic effects of pesticides, the actual impact of these phenomena remain largely unexplored. Here, we conducted a climate-controlled room experiment to assess the interactive effects of the projected 2100 climate scenario and environmentally realistic ATZ exposures on the reproductive function of male zebrafish. The gonadosomatic index significantly decreased in fish kept in the extreme scenario. Cellular alterations across spermatogenesis phases led to synergic decreased sperm production and increased germ cell sloughing and death. ATZ exposure alone or combined with climate change effects, disrupted the transcription levels of key genes involved in steroidogenesis, hormone signaling and spermatogenesis regulation. An additive modulation with decreased 11-KT production and increased E2 levels was also evidenced, intensifying the effects of androgen/estrogen imbalance. Moreover, climate change and ATZ independently induced oxidative stress, upregulation of proapoptotic gene and DNA damage in post-meiotic germ cell, but the negative effects of ATZ were greater at extreme scenario. Ultimately, exposure to simulated climate changes severely impaired fertilization capacity, due to a drastic reduction in sperm motility and/or viability. These findings indicate that the future climate conditions have the potential to considerably enhance the toxicity of ATZ at low concentrations, leading to significant deleterious consequences for fish reproductive function and fertility. These may provide relevant information to supporting healthcare and environmental managers in decision-making related to climate changes and herbicide regulation.
Keywords: Climate room, sperm motility; Herbicide; Sex hormones; Spermatogenesis